Flash cinematic techniques : enhancing animated shorts and interactive storytelling - Jackson, Chris (Chris B.); ScienceDirect eBooks (Oxford : Focal, 2010)
Apply universally accepted cinematic techniques to your Flash projects to improve the storytelling quotient in your entertainment, advertising (branding), and educational media. A defined focus on the concepts and techniques for production from story reels to the final project delivers valuable insights, time-saving practical tips, and hands-on techniques for great visual stories. Extensive illustration, step-by-step instruction, and practical exercises provide a hands-on perspective. Explore the concepts and principles of visual components used in stories so you are fluent in the use of space, line, color, and movement in communicating emotion and meaning. Apply traditional cinematography techniques into the Flash workspace with virtual camera movements, simulated 3d spaces, lighting techniques, and character animation. Add interactivity using ActionScript to enhance audience participation. * A unique focus on the principles and techniques of the visual art in storytelling. * Concepts are illustrated with deconstruction of technical issues, step-by-step instruction, and exercises. * Companion CD-ROM contains digital examples and media files for exercises.
Show ... Don't Tell Me a Story; Give Me Space; Direct My Eye; How Should I Feel?; Don't Lose Me; The Virtual Flash Camera; Simulating Lighting Techniques; Importance of Sound; Interactive Stories; Optimization; Publishing.
Print version record.
Elsevier
Safari Books Online
Keywords: Flash (Computer file); Flash (Computer file); Computer animation; COMPUTERS -- Digital Media -- General; COMPUTERS -- Web -- User Generated Content; COMPUTERS -- Interactive & Multimedia; COMPUTERS -- Web -- Site Design; Computer animation; Electronic books